Development of the soft-step javelin technique - Gorski, J. (1981)
The purpose of this article is to facilitate the training of javelin throwers, by means of explaining often-used terms and looking at the actual mechanics of the throw. Author believes that the training and performance of throwers would increase dramatically if the aura and mystery of the "European Technique" is cut away.